Does it pay to be different? An analysis of the relationship between corporate social and financial performance - Brammer, Stephen; Millington, Andrew (Strategic Management Journal, 2008)
Abstract This study explores the relationship between corporate social performance (CSP) and corporate financial performance (CFP) within the context of a specific component of CSP: corporate charitable giving. A model of the determinants of the extent of corporate charitable giving is estimated and used as the basis of a classification that groups firms according to the difference between their actual and their predicted intensity of gift giving. The financial performance attributes of the classification are explored. We found that firms with both unusually high and low CSP have higher financial performance than other firms, with unusually poor social performers doing best in the short run and unusually good social performers doing best over longer time horizons. Copyright © 2008 John Wiley & Sons, Ltd.